Microwave-assisted acid treatment for the mineral transformation of chrysotile as an alternative for asbestos waste management - Essih, Salima; Pardo, Laura; Cecilia-Buenestado, Juan Antonio; Dos-Santos-Gómez, Lucía; Pérez-Colodrero, Rosario Mercedes; Pozo, Manuel; Calero, Gustavo; Franco-Duro, Francisco Ignacio (Springer, 2024)
In this work, the efect of microwaveassisted acid treatments on the morphological and crystallochemical characteristics of chrysotile fbers is investigated. A low concentration of nitric acid (0.2 N) is used to remove Mg2+-species located in the octahedral sheet of its structure, thereby causing a crystallo-chemical change forming a skeleton of noncrystalline amorphous silica. This skeleton maintains an elongated morphology but characterized by rounded -not sharp-edges and porous surfaces whose physical resistance under stress is reduced when compared with the initial fbers of chrysotile, favoring a lower pathogenicity of the fbers. Thus, microwaveassisted acid treatment rise as a low-cost, fast and efective option in avoiding the dangerousness associated with asbestos waste management.
Keywords: Residuos - Gestión; Acid treatment; Microwave; Asbestos; Chrysotile